Keefektifan Media Gambar Seri dalam Pembelajaran Keterampilan Menulis Bahasa Jerman Level B1 pada Mahasiswa Semester 4 Prodi Pendidikan Bahasa Jerman FKIP Universitas HKBP Nommensen Pematang Siantar - Ita Purnamasari Sirait; Tarida Alvina Simanjuntak; Insenalia S.R Hutagalung (Departement of Mathematics Education, 2023)
This study aims: 1) To improve the writing skills of Semester 4 students of the German Language Study Program in learning writing skills by using picture series as media. 2) To find out the learning outcomes of picture series media for 4th semester German students. The population in this study were 4th semester German students at HKBP Nomensen Pematangsiantar University with a sample of 18 students. The data collection technique used in this study was through descriptive text techniques that the researcher had obtained. Based on the results of data analysis and the results of the hypotheses tested in this study, it can be seen that there is an increase in students' German writing skills before and after the application of picture series media. The results of the student test assessment on the pretest or before the application of serial picture media reached an average of 61.66 in the less category. The results of student test assessments at the posttest or after the application of serial picture media increased to 78.33 in the good category, therefore based on the results of the pretest and posttest there were differences in the results of writing skills for German Language Students Semester 4 at Nomensen University Pematangsiantar before and after applying the media series image. Based on the analysis of writing skills on the application of serial picture media in the Pretest and Posttest which states the level of sig (2-tailed) = 0.000 while this value is low compared to the significant value of ₁ which is 0.05 because it uses a significant level of 5% (0.000 <0.05) with once H₁ is accepted and H₀ is rejected, it means that there is a significant effect with the application of serial picture media on the writing skills of semester 4 students at HKBP Nommensen Pematang Siantar University.